2016
DOI: 10.3892/ol.2016.5136
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol reverses P-glycoprotein-mediated multidrug resistance of U2OS/ADR cells by suppressing the activation of the NF-κB and p38 MAPK signaling pathways

Abstract: Abstract. The present study aimed to investigate the reversal effect of resveratrol on the phenomenon of multidrug resistance in U2OS/adriamycin (ADR) cells and to clarify the molecular mechanisms. To examine the cell survival and half-inhibitory concentration (IC 50 ) of ADR in U2OS and U2OS/ADR cells, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was used. The accumulation of ADR in U2OS and U2OS/ADR cells was investigated by flow cytometry. Reverse transcription-quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that resveratrol causes decrease in MDR1 gene expression by inhibiting NF-kB activation as well as the signaling pathway of p38 MAPK (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that resveratrol causes decrease in MDR1 gene expression by inhibiting NF-kB activation as well as the signaling pathway of p38 MAPK (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…In human drug-resistant human breast cancer cells, P-gp was proposed to promote migration and invasion through its associations with ANXA2 ( 15 ). Another study on gastric cancer cells reported that ANXA2 stimulates the expression of P-gp and the development of drug resistance by activating MAPK signaling pathway ( 19 ). These findings support the theory that HE4, ANXA2 and P-gp act in concert to play significant roles in the malignant biological behavior of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have provided evidence of a significant association of ANXA2 with drug resistance in diverse malignant tumors (16)(17)(18). ANXA2 increases P-gp expression in gastric cancer cells by activating the MAPK signaling pathway, resulting in MDR of cancer cells (19).…”
Section: Human Epididymis Protein 4 Promotes P-glycoprotein-mediated Chemoresistance In Ovarian Cancer Cells Through Interactions With Anmentioning
confidence: 99%
“…After NF-κB nuclear translocation and binding to its recognition site, the promoter of the MDR1 gene is activated, and gene expression is induced. 17 , 18 , 34 , 35 Tomita et al found that CD133 regulates the level of MDR1/P-gp in glioblastoma through the PI3K/AKT-NF/κB signalling pathway, thereby promoting MDR. 36 Li et al reported that PKC DNA could regulate the expression of MDR1/P-gp in CD133-positive osteosarcoma cells through the PI3K/AKT/NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%